2011
DOI: 10.1007/s11605-011-1724-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentations and Surgical Approach of Acute Intussusception Caused by Peutz–Jeghers Syndrome in Adults

Abstract: Consecutive patients with the postoperative diagnosis of acute intussusception caused by Peutz-Jeghers syndrome from 1995 to 2010 were reviewed retrospectively for this study. Data concerning clinical considerations, morphological examinations, and surgical procedure were analyzed. Different clinical manifestations were presented in patients with intussusception due to Peutz-Jeghers syndrome. Computed tomography associated or not with ultrasonography may be the most accurate examination for acute intussuscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
4
30
0
Order By: Relevance
“…In our study, at the time of admission, seven patients (43.8 %) had diagnosed associated pathologies which could be responsible for the invagination, three (18.8 %) with PJS, and two (12.5 %) HIV positive. Although several reports identify these two pathologies as the underlying cause of AI [14,[21][22][23], others mention this only occurs rarely [24,25]. Given an overall 31.3 % of the studied patients had either PJS or HIV; our results support these two pathologies as a frequent cause of AI.…”
Section: Discussionsupporting
confidence: 71%
“…In our study, at the time of admission, seven patients (43.8 %) had diagnosed associated pathologies which could be responsible for the invagination, three (18.8 %) with PJS, and two (12.5 %) HIV positive. Although several reports identify these two pathologies as the underlying cause of AI [14,[21][22][23], others mention this only occurs rarely [24,25]. Given an overall 31.3 % of the studied patients had either PJS or HIV; our results support these two pathologies as a frequent cause of AI.…”
Section: Discussionsupporting
confidence: 71%
“…Abdominal CT scan provided the diagnosis of intussusception and identified the nature of the underlying pathology with a sensitivity rate of 100%. This agrees with Hong et al [24] who found that the spot diameter was between 2 and 5 mm. All the patients presented with an acute abdomen.…”
Section: Discussionsupporting
confidence: 93%
“…No postoperative complications were reported. These results are consistent with Hong et al [24] who studied 11 PJS patients with intussusception. All of them had a laparotomy with successful manual reduction of the intussusception.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The incidence has been estimated to be between 1 in 8,300 and 1 in 200,000 live births (4). The polyps are located predominantly in the small intestine, and may cause various complications, including abdominal pain, anemia and acute intussusceptions (5). Patients with Peutz-Jeghers syndrome have an increased risk of developing cancer or transformation to malignant polyps in the gastroinstestinal tract and other organs (6).…”
Section: Introductionmentioning
confidence: 99%